Viruses and cancer: lessons from the human polyomavirus, JCV - Reiss, Krzysztof; Khalili, Kamel (Oncogene, 2003)
The possible role of eucaryotic viruses in the development of cancer has been the subject of intense investigation during the past 50 years. Thus far, a strong link between some RNA and DNA viruses and various cancers in humans has been established and the transforming activity of several of the viruses in cell culture and their oncogenecity in experimental animals has been well documented. Perhaps, one of the most common themes among the oncogenic viruses rests in the ability of one or more of the viral proteins to deregulate pathways involved in the control of cell proliferation. For example, inactivation of tumor suppressors through their association with viral transforming proteins, and/or impairment of signal transduction pathways upon viral infection and expression of viral proteins are among the key biological events that can either trigger and/or contribute to the process of cancer. In recent years, more attention has been paid to human polyomaviruses, particularly JC virus (JCV), which infects greater than 80% of the human population, due to the ability of this virus to induce a fatal demyelinating disease in the brain, its presence in various tumors of central nervous system (CNS) and non-CNS origin, and the oncogenic potential of this virus in several laboratory animal models. Here, we will focus our attention on JCV and describe several pathways employed by the virus to contribute to and/or accelerate cancer development.